The Needs of English for Elementary School Students: from Family to School - Sukarno, Sukarno; Jinabe, Megan (Jurnal Prima Edukasia, 2024)
In accordance with Ki Hajar Dewantara's educational philosophy, which emphasizes the simultaneous role of home, school, and community in education, this study addresses a significant change in the Indonesian primary school curriculum. Several years ago, the Indonesian government removed English language instruction from elementary schools. However, the recently introduced Kurikulum Merdeka has reinstated English as a local subject in primary education. This reintroduction has generated concerns among TEYL (Teaching English for Young Learners) professionals, as it challenges the notion of the golden age of language acquisition. Young learners are believed to benefit from extensive exposure to the English language due to their rapid knowledge acquisition potential. Consequently, this study seeks to investigate the perspectives, interests, and needs of parents, teachers, and schools regarding the implementation of English language instruction at elementary schools. This quantitative cross-sectional study involved 383 participants selected through a purposive sampling strategy. It employed a survey research approach complemented by triangulation and Cronbach's Alpha tests to ensure validity and reliability. The findings of this research are poised to offer invaluable insights for parents seeking the best educational opportunities for their children and TEYL experts striving to enhance their teaching practices and methodologies. Additionally, this research highlights the demand for early childhood English language education. It serves as a foundational resource for evidence-based improvements in the educational landscape, ultimately benefiting the Indonesian youth as they navigate the complexities of the modern world.